A comparative study of essential oil constituents, total phenolics and antioxidant capacity of the different organs of four species of the genus bunium. (19th March 2021) - Adelifar, Najmeh; Rezanejad, Farkhondeh
Abstract: Bunium persicum is one of the fragrant herbaceous plants that has many nutritional and medicinal applications. Information about other species of Bunium is scarce. Essential oils, polyphenolics and antioxidant activity were analysed in four species of Bunium . The highest levels of total flavonoids were observed in leaves and fruits of B wolffii while the other polyphenolics did not show significant differences between the species and organs. Gas chromatography‐mass spectrometry (GC/MS) analysis revealed 16, 14, 14 and 13 main components respectively accounting for 97.52% of the entire essential oils of B cylindricum, 91.12% of B paucifolium, 97.14% B persicum and 96.41% of B wolffii . The monoterpenes content was 57.9, 22, 97.14 and 63.83% in B cylindricum, B paucifolium, B persicum and B wolffii respectively whereas sesquiterpenes levels were respectively 1.29, 27.45, 0.0 and 2.98%. The nonterpens constituted 38.33, 41.67, 0.0 and 29.6% in these four species respectively. The highest amount of monoterpenes (97.14%) was observed in B persicum, while the maximum of sesquiterpenes (27.45%) and nonterpenes (41.67%) obtained in B paucifolium . The main constituents were γ‐terpinene, myristicin, cuminaldehyde, apiole, α ‐pinene, β ‐pinene, β ‐selinene, Z ‐ β ‐ocimene and γ ‐terpinene‐7‐al. Cuminaldehyde with the pleasant odour was only revealed in B persicum . All organs of different species except corms showed high antioxidant activity using ABTS and DPPH assay. Thus, similar to B persicum, the other studied species are a rich source of antioxidant compounds and can be used as functional food ingredients and a potential source of natural antioxidants with valuable health benefits. Abstract : Important essential oils containing good antioxidant activity such as γ ‐ terpinene, myristicin, apiole, α ‐ pinene, β ‐ pinene, β ‐ selinene, Z ‐ β ‐ ocimene, γ ‐ terpinene‐7‐al and cumin aldehyde were revealed in different species of Bunium . The results obtained from this survey showed that similar to B persicum, the other studied species are a rich source of antioxidant compounds and have valuable health benefits. However, other species revealed any remarkable cumin aldehyde as seen in B persicum . So, they can use natural additives in the food and pharmaceutical industry.